2018
DOI: 10.3390/ijerph15040645
|View full text |Cite
|
Sign up to set email alerts
|

Factors that Predict Parental Willingness to Have Their Children Vaccinated against HPV in a Country with Low HPV Vaccination Coverage

Abstract: Background: Adolescent HPV (Human Papilloma Virus) vaccination is yet to be introduced as a mandatory program in Poland. Polish literature on factors associated with adolescent HPV vaccination is scant, despite the fact that uptake is one of the poorest in the European Union. Objectives: To assess HPV awareness and identify independent predictors for parental willingness to have their children vaccinated against HPV. Methods: All parents of first grade students from three selected high schools in Zgorzelec, Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(71 citation statements)
references
References 28 publications
4
64
2
1
Order By: Relevance
“…The high level of willingness shown by the respondents in this study (80.9%) to accept HPV vaccination for their daughters is consistent with the reports from previous studies in Poland among parents where a major proportion of the total respondents (85.1%) expressed their willingness to vaccinate their daughters against HPV infection [ 31 ]. This is also similar to another study in UAE where 76.6% of the respondents were willing to give their daughters HPV vaccine [ 32 ] and another study in Enugu, Nigeria where 91% of the respondents were willing to recommend it to their adolescent daughters [ 14 ].…”
Section: Discussionsupporting
confidence: 90%
“…The high level of willingness shown by the respondents in this study (80.9%) to accept HPV vaccination for their daughters is consistent with the reports from previous studies in Poland among parents where a major proportion of the total respondents (85.1%) expressed their willingness to vaccinate their daughters against HPV infection [ 31 ]. This is also similar to another study in UAE where 76.6% of the respondents were willing to give their daughters HPV vaccine [ 32 ] and another study in Enugu, Nigeria where 91% of the respondents were willing to recommend it to their adolescent daughters [ 14 ].…”
Section: Discussionsupporting
confidence: 90%
“…it showed that only 29% of the respondents had heard of hPV, and few knew that it is associated with cervical cancer. in a Polish survey, almost half of 450 parents of high school students who participated in the study (44.7%) had never heard of hPV [20]. regarding parents' attitudes toward hPV, 92% stated that vaccines are effective in disease prevention, and 43.1% were concerned about the possible side effects of vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…It is still speculated that being employed, high income earner and married are associated with, or constitute positive influence for acceptance of cervical services. 14,15 However, the background literature indicate dearth of research investigation on the odds of women's acceptance of both cervical cancer screening and HPV vaccination. Thus, there may be erroneous assumption that affordability is a reason for accepting any of these services.…”
Section: Discussionmentioning
confidence: 99%